Barriers to accessing adequate maternal care in Georgia: a qualitative study - Elina Miteniece; Milena Pavlova; Lela Shengelia; Bernd Rechel; Wim Groot (BMC, 2018)
Abstract Background The maternal health outcomes in Georgia are linked to shortcomings in healthcare such as inequities in access to adequate maternal care. Due to the macro-level, quantitative approach applied in most previous studies, little is known about the underlying reasons that influence maternal care and care-seeking behaviour of pregnant women. Methods This qualitative study explores the stakeholders' perspectives on access to adequate maternal care in Georgia. Focus-group discussions are conducted with mothers who gave birth within in the past four years and in-depth interviews are conducted with decision-makers and health professionals in the field. Five access-related aspects are studied: availability, appropriateness, affordability, approachability and acceptability of maternal care. The method of direct content analysis is applied. Results Results indicate problems with maternal care standards, inequalities across population groups and drawbacks in maternal care financing. This includes gaps in clinical quality and staff skills, as well as poor communication between women and health professionals. Geographical barriers to adequate maternal care exist in rural and mountainous areas due to the weak infrastructure (poor roads and weak transportation), in addition to financial hardships. Despite improvements in the coverage of maternal care, affordability remains an access barrier. Poorer population groups are financially unprotected from the high out-of-pocket payments for maternal care services. Conclusion These findings imply that micro-level indicators, such as disrespectful behaviour of health professionals and affordability of care, should be taken into account when assessing maternal care provision in Georgia. It should complement the existing macro-level indicators for a comprehensive evaluation of maternal care.